A conductive film with regular micro-nano cone array structure, preparation method and application thereof
By preparing conical anodized aluminum template on an aluminum substrate, and combining chemical in-situ polymerization and spin coating, a regular micro-nanocone array structure conductive film was prepared, which solved the problem of complex mold preparation and difficult to adjust the microstructure size in the prior art, and realized the adjustability and preparation of nanocones in the conductive film.
Patent Information
- Application Number
- CN202210848572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-20
- Filing Date
- 2022-07-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-07-19
AI Technical Summary
In the prior art, when preparing microstructured conductive films, the mold preparation is complex, the equipment is highly dependent, and the microstructure size is difficult to adjust, resulting in the microstructure of the conductive film being mainly at the micron level.
Single-layer or double-layer conical anodized aluminum template was prepared by anodizing method, combined with chemical in-situ polymerization method and spin coating method, conductive polymer and flexible polymer layers were synthesized, and the template was then removed in aqueous phosphoric acid solution to prepare a regular micro-nano conical array structure conductive film.
The adjustment of the nanocone size in the conductive film within the nanometer range was achieved, and an interlocking piezoresistive sensor with high sensitivity was prepared, which had the advantages of low voltage, high sensitivity, high precision and miniaturization.
Smart Images

Figure CN115159448B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material technology, and in particular relates to a conductive film with a regular micro-nano cone array structure, and a preparation method and application thereof. Background Art
[0002] Bio-inspired micro-nanostructured films are considered to be one of the promising materials for making highly sensitive sensors. The biomimetic structures mainly include interlocking, cracks, whiskers, human skin and fingerprint structures. Among them, micro-nano interlocking sensors have attracted the research and attention of many scholars due to their combination of microstructures and interlocking structures. Cheng et al. coated graphene on a PDMS array using micromachining and micromanipulation technology and prepared a sensor with a sensitivity of 10.41 kPa. -1 Interlocking pressure sensor (Cheng L, Qian W, et al. J. Mater. Chem. C, 2020, 8(33): 11525-11531). Ha et al. prepared a flexible piezoresistive sensor using PDMS micropillars coated with ZnO nanowires, with a sensitivity of 6.8 kPa. -1 (Ha M, Lim S, et al. Advanced Functional Materials, 2015, 25: 2841-2849.) Park et al. designed an interlocking microsphere structure that mimics human skin, thereby preparing a sensitive 15.1 kPa -1 Sensors (Park J, Lee Y, et al. ACS Nano, 2014, 8(5): 4689-4697).
[0003] However, the molds for preparing microstructures are mainly silica [Lee Y, Park J, ACS Nano, 2018, 12(4): 4045-4054] and natural biomaterials [Wan Y, Qiu Z, Small, 2018, 14(35): 1-8]. The preparation of silica templates requires the use of traditional photolithography technology, which has a complex preparation process, strong equipment dependence and high manufacturing cost. Due to the inherent properties of the microstructure of natural biomaterials, the geometric microstructure size is not adjustable, and the microstructure of the conductive film prepared using the above molds is mostly at the micron level. Summary of the invention
[0004] One object of the present invention is to provide a method for preparing a conductive film having a regular micro-nanocone array structure;
[0005] Another object of the present invention is to provide a method for preparing an interlocking piezoresistive sensor using the conductive film prepared by the above method.
[0006] To this end, the present invention adopts the following technical solutions:
[0007] A method for preparing a conductive film with a regular micro-nano cone array structure comprises the following steps:
[0008] (1) A single-layer or double-layer conical anodized aluminum template is prepared on an aluminum substrate by an anodizing method;
[0009] (2) using a chemical in-situ polymerization method to polymerize a monomer of a conductive polymer onto the pore wall of the single-layer or double-layer conical anodized aluminum template obtained in step (1), wherein the monomer of the conductive polymer is pyrrole, aniline or thiophene;
[0010] (3) spin coating a solution of a flexible polymer onto the single-layer or double-layer conical alumina template with a conductive polymer attached to the surface obtained in step (2) by a spin coating method, and then placing the template in a vacuum drying oven for high-temperature treatment under vacuum conditions, wherein the flexible polymer is polymethyl methacrylate, polystyrene, polyurethane or polyacrylonitrile;
[0011] (4) placing a single-layer or double-layer conical anodized aluminum template with an aluminum substrate and a conductive polymer and a flexible polymer composite coating on the surface after vacuum high temperature treatment into a mixed solution of hydrochloric acid and copper chloride to remove the aluminum substrate;
[0012] (5) placing the single-layer or double-layer conical anodized aluminum template with a conductive polymer and a flexible polymer composite coating on its surface obtained in step (4) in a phosphoric acid aqueous solution to remove the conical anodized aluminum template and obtain a single-layer or double-layer regular micro-nanocone array structure conductive film.
[0013] Wherein, when preparing a single-layer conical alumina template in step (1), the reaction solution is a mixture of 1wt% H3PO4 and 0.03-0.3M C2H2O4, the oxidation voltages are 200V, 190V, 180V, 170V, 150V, and 130V, respectively, decreasing in sequence, and the corresponding C2H2O4 concentrations are 0.03M, 0.05M, 0.07M, 0.1M, 0.2M, and 0.3M, respectively, increasing in sequence, and the reaction time is 10-40min; the method for preparing a double-layer conical alumina template is to anodize the single-layer conical anodized aluminum template in a 0.1-0.4M oxalic acid solution for 0.5-30min, and the reaction temperature is 0-3°C.
[0014] The specific method of step (2) is as follows: immersing the aluminum substrate with conical anodized aluminum oxide on the surface into an aqueous solution of a conductive polymer monomer with a concentration of 0.2-0.4M, magnetically stirring for 20-35 minutes, and then adding an equal volume of a mixed aqueous solution containing 0.3-0.7M p-toluenesulfonic acid and 0.3-0.6M ferric chloride, and polymerizing for 40-80 minutes under magnetic stirring conditions.
[0015] Preferably, in step (3), the solvent of the flexible polymer solution is N,N-dimethylformamide, the solute mass fraction is 10-25wt%, the spin coater speed is 500-4000r / min, the spin coating time is 10-30s; the vacuum drying oven temperature is 80-160°C, and the time is 1-3.5h.
[0016] Preferably, in step (4), the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and cupric chloride is 5-25wt%, and the concentration of cupric chloride is 0.05-0.15mol / L.
[0017] Preferably, in step (5), the mass fraction of the phosphoric acid aqueous solution is 10-30wt%, and the reaction temperature is 20-60°C.
[0018] A regular micro-nano cone array structure conductive film prepared by the above preparation method, wherein the diameter of the micro-nano cones of the single-layer regular micro-nano cone array structure conductive film is 50nm-500nm, and the height is 100nm-20μm; in the double-layer regular micro-nano cone array structure conductive film, the diameter of the bottom layer nanocolumns is 50nm-500nm, and the height is 100nm-20μm, and the diameter of the top layer nanocolumns is 50nm-100nm, and the height is 10nm-1000nm.
[0019] An application of the above-mentioned regular micro-nanocone array structure conductive film in the preparation of an interlocking piezoresistive sensor. First, two pieces of the regular micro-nanocone array structure conductive film are taken, and a strip conductive electrode is respectively pasted on the same side edge of the two conductive films with nanocones using conductive silver glue, and naturally dried at room temperature; then the nanocone surfaces of the above-mentioned two conductive films are placed face to face, and the two strip electrodes are extended in the same direction, and then packaged to obtain the interlocking piezoresistive sensor.
[0020] Preferably, the size of the regular micro-nanocone array structure conductive film is (1-2) cm*(1-2) cm; the strip conductive electrode is a copper sheet, a gold sheet, a titanium sheet or a platinum sheet, or a magnetron sputtered copper, platinum, titanium or a composite coating electrode thereof.
[0021] The packaging method is to use a flexible tape for packaging, and the flexible tape is a polyvinyl chloride tape or a polyurethane tape. The present invention uses a conical anodized aluminum as a template, adopts an in-situ polymerization method and a polymer spin coating method, and dissolves the conical anodized aluminum in a phosphoric acid aqueous solution to prepare a regular micro-nano conical array structure conductive film, and then uses an interlocking structure to package it into an interlocking piezoresistive sensor.
[0022] The present invention has the following beneficial effects:
[0023] (1) The single-layer or double-layer anodized aluminum template used in the present invention is a hexagonal continuous structure in which holes are perpendicular to the aluminum substrate and arranged in parallel, and has the characteristics of highly ordered structure, large specific surface area, etc., and the size is adjustable in the nanometer range. Therefore, the diameter of the nanocones in the prepared single-layer conductive film is adjustable in the range of 50-500nm and the height is adjustable in the range of 100nm-20μm; the diameter of the bottom nanocolumn in the double-layer hierarchical structure conductive film can be 50nm-500nm and the height can be 100nm-20μm, while the diameter of the top nanocolumn can be 50nm-100nm and the height can be 0nm-1000nm;
[0024] (2) The regular micro-nano cone array structure conductive film structure prepared by the present invention presents a cone array structure with a flexible polymer as the core and a conductive polymer as the shell, which has both the conductivity of the conductive polymer and the flexibility of the flexible polymer, and can therefore be used to prepare a flexible pressure sensor;
[0025] (3) The size of the regular micro-nanocone array structure conductive film prepared in the embodiment of the present invention is 1 cm*1 cm, and the thickness is only 1460 nm (Example 1), which provides a basis for preparing miniaturized sensors; the regular nanocone structure is more sensitive to tiny weak pressure due to its nanometer size and large specific surface area, so that the sensor prepared by it has ultra-high sensitivity;
[0026] (4) The interlocked piezoresistive sensor is prepared by using an interlocking packaging structure. The interlocking makes the nanocones contact each other face to face, which effectively increases the contact area between the nanocones and further increases the sensitivity of the sensor. The interlocked piezoresistive sensor has the advantages of low pressure, high sensitivity, high precision and miniaturization.
[0027] (5) The present invention uses a template method to combine a conductive polymer and a flexible polymer. The method is simple and feasible, and the prepared film is highly regular, with a flexible polymer as a core and a conductive polymer as a shell, presenting a conical array structure. The conductive film has both the conductivity of the conductive polymer and the flexibility of the flexible polymer, and the film structure is stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1a is a SEM image of a single-layer micro-nano cone array structure conductive film prepared in Example 1 of the present invention;
[0029] Figure 1b is a SEM image of a conductive film with a double micro-nanocone array structure prepared in Example 3 of the present invention;
[0030] Figure 2a This is a physical picture of a single-layer micro-nano cone array structure PPy film prepared in Example 1 of the present invention;
[0031] Figure 2bThis is a physical picture of the single-layer nanocone array flexible conductive polymer PPy@PMMA film prepared in Example 1 of the present invention;
[0032] Figure 3 is a schematic diagram of the exploded structure of the interlocking piezoresistive sensor prepared in Example 1 of the present invention;
[0033] Figure 4 is a schematic structural diagram of an interlocking piezoresistive sensor prepared in Example 1 of the present invention;
[0034] Figure 5 This is a schematic diagram of the compression principle of the interlocking structure of the single-layer micro-nano cone array conductive film prepared in Example 1;
[0035] Figure 6 This is a schematic diagram of the compression principle of the interlocking structure of the double-layer micro-nano cone array conductive film with small hole spacing prepared in Example 2;
[0036] Figure 7 This is a schematic diagram of the compression principle of the interlocking structure of the double-layer micro-nano cone array conductive film with large pore spacing prepared in Example 3;
[0037] Figure 8 a is a piezoresistive test diagram of the sample prepared in Example 1 of the present invention;
[0038] Figure 8 b is a piezoresistive test diagram of the sample prepared in Example 2 of the present invention;
[0039] Figure 8 c is a piezoresistive test diagram of the sample prepared in Example 3 of the present invention;
[0040] In the figure:
[0041] 1. Polyvinyl chloride tape 2. Strip electrode 3. Regular micro-nano cone array structure conductive film DETAILED DESCRIPTION
[0042] The method of the present invention is described in detail below with reference to specific embodiments.
[0043] Before the following examples are carried out, the aluminum sheet is pretreated and pre-oxidized, and the specific method is as follows:
[0044] A high-purity aluminum sheet with a purity of 99.999% was ultrasonically cleaned in acetone for 15 minutes to remove grease on the surface, then washed with deionized water, and then placed in a 1 mol / L NaOH solution for 10 minutes to remove the natural oxide layer on the surface, and finally washed and dried with deionized water; the dried aluminum sheet was used as the anode and the titanium plate as the cathode, and electrochemical polishing was performed for 5 minutes at a voltage of 21V and a temperature of 0-5°C in a mixture of perchloric acid and anhydrous ethanol in a solution volume ratio of 1:4 to obtain an aluminum sheet with a smooth surface.
[0045] The pretreated aluminum sheet was used as the anode and the titanium plate as the cathode, and a mixed solution containing 0.03M oxalic acid and 1wt% phosphoric acid (i.e., the concentrations of oxalic acid and phosphoric acid in the mixed solution are 0.03M and 1wt%, respectively, the same below) was used as the electrolyte for the first anodic oxidation. The oxidation voltage was 200V, the temperature was 0-3°C, and the oxidation time was 4h. The aluminum oxide film with an aluminum substrate after the first oxidation was placed in a mixed solution containing 18g / L CrO3 and 6wt% H3PO4, the reaction temperature was 60°C, the generated aluminum oxide was removed, and an aluminum sheet with regular pits was obtained.
[0046] The solutions described in the following examples are all aqueous solutions unless otherwise specified.
[0047] The technical solution of the invention is further illustrated by means of specific embodiments below.
[0048] Example 1
[0049] A method for preparing a single-layer regular micro-nano cone array structure conductive film comprises the following steps performed in sequence:
[0050] (1) The aluminum sheet with regular pits is anodized again under the same conditions as the first anodization. After oxidation for 2 minutes, it is chemically etched in a 5wt% phosphoric acid solution for 45 minutes. After chemical etching, it is anodized again for 2 minutes, chemically etched in a 5wt% phosphoric acid solution for 45 minutes, and finally, it is anodized for 2 minutes and chemically etched in a 5wt% phosphoric acid solution for 90 minutes, so that a highly ordered single-layer conical anodic aluminum oxide (AAO) template can be obtained;
[0051] (2) The AAO template prepared in step (1) was immersed in a 10 ml 0.3 M pyrrole aqueous solution and magnetically stirred for 30 min (the volume of the beaker used was 25 ml) so that the pyrrole aqueous solution could fully enter the pores of the AAO template; then 10 ml of a mixed aqueous solution containing 0.5 M dopant p-toluenesulfonic acid and 0.45 M oxidant ferric chloride was added and polymerized for 60 min, and the process was also carried out under magnetic stirring; then the conical anodized aluminum template coated with polypyrrole was taken out and dried naturally;
[0052] (3) dripping a 20 wt % polymethyl methacrylate solution onto the conical anodized aluminum template with polypyrrole obtained in step (2), with the spin coater rotating at 800 / min and the spin coating time being 30 s; after spin coating, placing the template in a vacuum drying oven, setting the temperature at 150° C. under vacuum, maintaining the temperature for 2 h, and then cooling the template naturally to room temperature;
[0053] (4) removing the aluminum substrate from the single-layer conical anodized aluminum template (with a conductive polymer and a flexible polymer composite coating on the surface) obtained in step (3) in a mixed solution containing 10% hydrochloric acid and 0.1 mol / L copper chloride;
[0054] (5) The anodized aluminum template obtained in step (4) is reacted in a 30° C., 20 w % phosphoric acid solution to remove the cone-shaped anodized aluminum template, thereby obtaining a single-layer regular micro-nano cone array structure conductive film.
[0055] The FESEM image of the single-layer regular micro-nanocone array structure conductive film is attached. Figure 1a , and the height of the nanocone is 1460nm. The cross section shows that the diameter of the nanocone gradually increases from top to bottom. The height and diameter of the nanocone structure can be continuously adjusted in the range of 50-500nm in diameter and 100nm-20μm in height by changing the size of the AAO template. The corresponding relationship between the oxidation time and the height of the nanocone is regulated by changing the second oxidation time in step (1). Specifically, the second oxidation time in step (1) is 2min, and the oxidation is performed 3 times, and the corresponding nanocone height is 1460nm. The specific parameters for regulating the height of the nanocone by changing the oxidation time are shown in Table 1.
[0056] Table 1 Second oxidation time and the height of the corresponding nanocones prepared
[0057]
[0058] Example 2
[0059] A method for preparing a double-layer micro-nano cone array structure conductive film comprises the following steps performed in sequence:
[0060] (1) The aluminum sheet with regular pits was anodized again under the same conditions as the first anodization. After oxidation for 2 minutes, it was chemically etched in a 5wt% phosphoric acid solution for 15 minutes. After chemical etching, it was anodized again for 2 minutes and chemically etched in a 5wt% phosphoric acid solution for 15 minutes. The oxidation and pore expansion time were alternated 4 times, and the second oxidation was completed;
[0061] (2) placing the aluminum sheet after secondary oxidation in a 0.15 M oxalic acid solution at an oxidation voltage of 100 V and an oxidation time of 140 s, and then chemically etching it in a 5 wt % phosphoric acid solution for 30 min to obtain a double-layer conical anodic aluminum oxide (AAO) template;
[0062] (3) The prepared AAO template was immersed in a 10 ml 0.3 M pyrrole aqueous solution and magnetically stirred for 30 min (the beaker volume was 25 ml) to allow the pyrrole aqueous solution to fully enter the pores of the AAO template; then 10 ml of a mixed aqueous solution containing 0.5 M dopant p-toluenesulfonic acid and 0.45 M oxidant ferric chloride was added and polymerized for 60 min, and the process was also carried out under magnetic stirring; then the conical anodized aluminum template coated with polypyrrole was taken out and dried naturally;
[0063] (4) dripping a 20 wt % polymethyl methacrylate solution onto the conical anodized aluminum template with polypyrrole obtained in step (2), with the spin coater rotating at 800 / min and the spin coating time being 30 s; after spin coating, placing the template in a vacuum drying oven, setting the temperature at 150° C. under vacuum, maintaining the temperature for 2 h, and then cooling the template naturally to room temperature;
[0064] (5) removing the unreacted aluminum matrix from the conical anodized aluminum template with an aluminum substrate in a mixed solution containing 10% hydrochloric acid and 0.1 mol / L copper chloride.
[0065] (6) The cone-shaped anodized aluminum template is removed by reaction in a 20w% phosphoric acid solution at 30°C to obtain a double-layer regular micro-nano cone array structure conductive film.
[0066] The nanocone array flexible conductive polymer film presents a hierarchical structure. On the basis of the bottom nanocone, about 3-4 top nanocones grow. The bottom nanocone has a diameter of 215nm, which can achieve hierarchical nanocone cross-interlocking. The bottom nanocone diameter in the hierarchical micro-nanocone with small hole spacing is adjustable in the range of 50-250nm and the height is 100nm-20μm; the top nanocolumn diameter can be continuously adjusted in the range of 50nm-100nm and the height is 0nm-1000nm.
[0067] Example 3
[0068] A method for preparing a conductive film having a double-layer regular micro-nano cone array structure with a large pore spacing comprises the following steps performed in sequence:
[0069] (1) The aluminum sheet with regular pits was anodized again under the same conditions as the first anodization. After oxidation for 2 minutes, chemical etching was performed in a 5wt% phosphoric acid solution for 37.5 minutes. After chemical etching, anodization was performed again for 2 minutes, and chemical etching was performed in a 5wt% phosphoric acid solution for 37.5 minutes. The oxidation and pore expansion time were alternated 4 times, and the second oxidation was completed;
[0070] (2) The aluminum sheet after secondary oxidation was placed in a 0.15 M oxalic acid solution, with an oxidation voltage of 100 V and an oxidation time of 140 s, and then chemically etched in a 5 wt % phosphoric acid solution for 30 min to obtain an AAO template with a large pore spacing hierarchical structure;
[0071] (3) The prepared AAO template was immersed in a 10 ml 0.3 M pyrrole aqueous solution and magnetically stirred for 30 min (the beaker volume was 25 ml) to allow the pyrrole aqueous solution to fully enter the pores of the AAO template; then 10 ml of a mixed aqueous solution containing 0.5 M dopant p-toluenesulfonic acid and 0.45 M oxidant ferric chloride was added and polymerized for 60 min, and the process was also carried out under magnetic stirring; then the conical anodized aluminum template coated with polypyrrole was taken out and dried naturally;
[0072] (4) dripping a 20 wt % polymethyl methacrylate solution onto the conical anodized aluminum template with polypyrrole obtained in step (2), with the spin coater rotating at 800 / min and the spin coating time being 30 s; after spin coating, placing the template in a vacuum drying oven, setting the temperature at 150° C. under vacuum, maintaining the temperature for 2 h, and then cooling the template naturally to room temperature;
[0073] (5) removing the unreacted aluminum matrix in a mixed solution containing 10% hydrochloric acid and 0.1 mol / L copper chloride,
[0074] (6) The cone-shaped anodized aluminum template is removed by reaction in a 20w% phosphoric acid solution at 30°C to obtain a double-layer regular micro-nano cone array structure conductive film with a large pore spacing.
[0075] The FESEM image of the nanocone array flexible conductive polymer film is shown in Figure 1b , presenting a hierarchical structure. On the basis of the large nanocone, about 3-4 small nanocones grow. The length of the bottom nanocone is about 1.67um, the diameter is about 325nm, and the length of the top nanocone is about 264nm. In the macropore spacing hierarchical micro-nanocone, the bottom nanocone has an adjustable diameter of 250-500nm and a height of 100nm-20μm; the diameter of the top nanocolumn can be continuously adjusted from 50nm-100nm and the height can be continuously adjusted from 0nm-1000nm.
[0076] In the above three embodiments, the conductive polymer may be polypyrrole, polyaniline or polythiophene; the flexible polymer may be polyurethane, polystyrene or polyacrylonitrile.
[0077] Analysis of the physical image of nanocone array conductive polymer
[0078] Figure 2aShown is a physical picture of the nanocone array PPy conductive polymer film. It can be seen that there are many cracks on the surface of the nanocone array conductive polymer PPy film, which makes it impossible to form a complete conductive network. Moreover, due to poor mechanical properties, the PPy film cannot return to its original shape after compression.
[0079] In contrast, see Figure 2b The actual picture of the nanocone array flexible conductive polymer PPy@PMMA prepared in Example 1 of the present invention is shown. It can be seen from the picture that the film is a complete conductive film with no cracks on the surface. The picture shows that PPy@PMMA has good flexibility and can be bent freely, which provides a good basis for preparing flexible sensors. It can be seen that the introduction of the PMMA layer improves the flexibility of the PPy film, making it have elastic recovery properties, so it can be used to make flexible pressure sensors.
[0080] Example 4 Preparation of interlocked piezoresistive sensor
[0081] See also Figure 3 First, use conductive silver glue to bond the strip electrode 2 to one side of the nanocone surface of the regular micro-nanocone array structure conductive film 2, and dry it naturally at room temperature (time is about 12 hours), where the size of the regular micro-nanocone array structure conductive film is 1cm*1cm, and the size of the copper sheet electrode is 50mm*2mm; then place the nanocone surfaces of the two regular micro-nanocone array structure conductive films bonded with copper sheet electrodes face to face, and then package them with polyvinyl chloride tape 1 to obtain an interlocking piezoresistive sensor, where the size of the polyvinyl chloride tape is 1.5cm*1.5cm. The prepared interlocking piezoresistive sensor is as follows Figure 4 shown.
[0082] Analysis of compression mechanism
[0083] See also Figure 5 The interlocking piezoresistive sensor is prepared using the single-layer micro-nanocone array structure conductive film prepared in Example 1. When no pressure is applied, the single-layer micro-nanocones cross-contact each other in an interlocking structure. As the pressure increases, the first stage is the displacement of the micro-nanocones and the increase of the contact area; the second stage is the compression deformation of the micro-nanocones.
[0084] See also Figure 6 The interlocking sensor is assembled using a double-layer micro-nanocone structure conductive film with a small hole spacing prepared in Example 2. When no pressure is applied, the double-layer micro-nanocones cross-contact each other in an interlocking structure. As the pressure increases, the first stage is the displacement of the double-layer micro-nanocones, and the contact area of the bottom layer of micro-nanocones increases; the second stage is the extrusion deformation of the top layer of micro-nanocones, and the contact area further increases; the third stage is the compression deformation of the double-layer micro-nanocones.
[0085] See also Figure 7 The interlocking sensor is assembled using a double-layer micro-nanocone structure conductive film with a large pore spacing prepared in Example 2. When no pressure is applied, the top-layer micro-nanocones cross-contact each other in an interlocking structure. As the pressure increases, the first stage is the extrusion deformation of the top-layer micro-nanocones, and the contact area increases; the second stage is the compression deformation of the top-layer micro-nanocones; and the third stage is the compression deformation of the bottom-layer micro-nanocones.
[0086] Sensitivity Analysis of Interlocked Piezoresistive Sensors
[0087] Figure 8 ac are the piezoresistive test graphs of the interlocking piezoresistive sensors made of the nanocone array flexible conductive polymer films prepared in Examples 1-3, respectively. The graphs show that the resistance change rate increases with the increase of pressure. The sensitivity calculation formula is:
[0088]
[0089] Among them, S is sensitivity and P is pressure.
[0090] Then calculate the sensitivity according to the sensitivity calculation formula.
[0091] Figure 8 a Analysis shows that when the pressure is 0.5 kPa, the sensitivity of the interlocking piezoresistive sensor assembled by the nanocone array PPy@PMMA conductive film prepared in Example 1 is 100.86 kPa -1 , the measuring range is 0-5kPa, and the sensitivity value is much greater than the sensor sensitivity value reported in existing research;
[0092] Figure 8 b Analysis shows that when the pressure is 0.5 kPa, the sensitivity of the interlocking piezoresistive sensor assembled by the nanocone array PPy@PMMA conductive film prepared in Example 2 is 58.52 kPa -1 , the measuring range is 0-12kPa, and the sensitivity value is greater than the sensor sensitivity value reported in existing research;
[0093] Figure 8 c Analysis shows that when the pressure is 0.5 kPa, the sensitivity of the interlocking piezoresistive sensor assembled by the nanocone array PPy@PMMA conductive film prepared in Example 3 is 43.39 kPa -1 The sensitivity value is greater than the sensor sensitivity value reported in existing studies, and the measuring range is 0-21kPa, which is much larger than the effective range of micro-nanostructure sensors of the same scale.
Claims
1. A method for preparing a conductive film with a regular micro-nanocone array structure, comprising the following steps: (1) A single-layer or double-layer conical anodized aluminum template is prepared on an aluminum substrate by an anodizing method; (2) using a chemical in-situ polymerization method to polymerize a monomer of a conductive polymer onto the pore wall of the single-layer or double-layer conical anodized aluminum template obtained in step (1), wherein the monomer of the conductive polymer is pyrrole, aniline or thiophene; (3) spin coating a solution of a flexible polymer onto the single-layer or double-layer conical alumina template with a conductive polymer attached to the surface obtained in step (2) by a spin coating method, and then placing the template in a vacuum drying oven for high-temperature treatment under vacuum conditions, wherein the flexible polymer is polymethyl methacrylate, polystyrene, polyurethane or polyacrylonitrile; (4) placing a single-layer or double-layer conical anodized aluminum template with an aluminum substrate and a conductive polymer and a flexible polymer composite coating on the surface after vacuum high temperature treatment into a mixed solution of hydrochloric acid and copper chloride to remove the aluminum substrate; (5) placing the single-layer or double-layer conical anodized aluminum template with a composite coating of a conductive polymer and a flexible polymer on the surface obtained in step (4) in a phosphoric acid aqueous solution to remove the conical anodized aluminum template, thereby obtaining a single-layer or double-layer regular micro-nanocone array structure conductive film; When preparing a single-layer conical alumina template in step (1), the reaction solution is a mixture of 1wt% H3PO4 and 0.03-0.3M C2H2O4, the oxidation voltage is 200V, 190V, 180V, 170V, 150V, 130V, respectively, decreasing in sequence, the corresponding C2H2O4 concentrations are 0.03M, 0.05M, 0.07M, 0.1M, 0.2M, 0.3M, respectively, increasing in sequence, and the reaction time is 10-40min; The method for preparing the double-layer conical aluminum oxide template is to anodic-oxidize the single-layer conical anodized aluminum oxide template in a 0.1-0.4M oxalic acid solution for 0.5-30 minutes at a reaction temperature of 0-3°C.
2. The preparation method according to claim 1, characterized in that: The specific method of step (2) is: immersing the aluminum substrate with conical anodized aluminum oxide on the surface into an aqueous solution of a conductive polymer monomer with a concentration of 0.2-0.4M, magnetically stirring for 20-35 minutes, and then adding an equal volume of a mixed aqueous solution containing 0.3-0.7M p-toluenesulfonic acid and 0.3-0.6M ferric chloride, and the polymerization time under magnetic stirring conditions is 40-80 minutes.
3. The preparation method according to claim 1, characterized in that: In step (3), the solvent of the flexible polymer solution is N,N-dimethylformamide, the solute mass fraction is 10-25wt%, the spin coater speed is 500-4000r / min, the spin coating time is 10-30s; the vacuum drying oven temperature is 80-160°C, and the time is 1-3.5h.
4. The preparation method according to claim 1, characterized in that: In step (4), the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and cupric chloride is 5-25wt%, and the concentration of cupric chloride is 0.05-0.15mol / L.
5. The preparation method according to claim 1, characterized in that: In the step (5), the mass fraction of the phosphoric acid aqueous solution is 10-30wt%, and the reaction temperature is 20-60°C.
6. A conductive film with a regular micro-nanocone array structure prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The diameter of the micro-nanocones of the single-layer regular micro-nanocone array structure conductive film is 50nm-500nm, and the height is 100nm-20μm; in the double-layer regular micro-nanocone array structure conductive film, the diameter of the bottom layer nanocolumns is 50nm-500nm, and the height is 100nm-20μm, and the diameter of the top layer nanocolumns is 50nm-100nm, and the height is 10nm-1000nm.
7. An application of the conductive film with regular micro-nano cone array structure as claimed in claim 6 in preparing an interlocking piezoresistive sensor, characterized in that: First, two pieces of the regular micro-nanocone array structure conductive film are taken, and a strip conductive electrode is pasted on the same side edge of the two conductive films with nanocones using conductive silver glue, and they are naturally dried at room temperature; then the nanocone surfaces of the two conductive films are placed face to face, and the two strip electrodes are extended in the same direction, and then packaged to obtain the interlocking piezoresistive sensor.
8. The use according to claim 7, characterized in that: The size of the regular micro-nano cone array structure conductive film is (1-2) cm*(1-2) cm; the strip conductive electrode is a copper sheet, a gold sheet, a titanium sheet or a platinum sheet, or a magnetron sputtered copper, platinum, titanium or a composite coating electrode thereof.
9. The use according to claim 7, characterized in that: The packaging method is packaging with a flexible tape, and the flexible tape is a polyvinyl chloride tape or a polyurethane tape.